α-Copaene is a potent repellent against the Asian Citrus Psyllid Diaphorina citri - Rodrigo Facchini Magnani; Haroldo Xavier Linhares Volpe; Rejane Angélica Grigio Luvizotto; Tatiana Aparecida Mulinari; Thiago Trevisoli Agostini; Jairo Kenupp Bastos; Victor Pena Ribeiro; Michele Carmo-Sousa; Nelson Arno Wulff; Leandro Peña; Walter S. Leal (Scientific Reports)
Abstract The Asian Citrus Psyllid (ACP), Diaphorina citri, severely threatens citrus production worldwide by transmitting the greening (= Huanglongbing)—causing bacterium Candidatus Liberibacter asiaticus. There is growing evidence that the push-pull strategy is suitable to partially mitigate HLB by repelling ACP with transgenic plants engineered to produce repellents and attracting the vector to plants with a minimal disease transmission rate. Species that pull ACP away from commercial citrus plants have been identified, and transgenic plants that repel ACP have been developed. The concept of a repellent-producing plant was first demonstrated with an Arabidopsis line engineered to overexpress a gene controlling the synthesis of β-caryophyllene and other sesquiterpenes. We have analyzed the volatile organic compounds released by this Arabidopsis line and identified α-humulene, α-copaene, and trace amounts of β-elemene, in addition to β-caryophyllene. Behavioral measurements demonstrated that α-copaene repels ACP at doses ca. 100× lower than those needed for β-caryophyllene repellence. In contrast, α-humulene is innocuous at the level emitted by the transgenic plant. We confirmed that a mixture of the three sesquiterpenes in the ratio 1:100:10 repels ACP. Likewise, a commercial sample of copaiba oil containing the three sesquiterpenes, in a proportion similar to that in the transgenic plant, repelled ACP.